Knowing the Real in Debra Granik’s Winter’s Bone - Ellie RAGLAND (E-REA)
Winter’s Bone, a film by Debra Granik (2010), tells the story of Ree Dolly’s refusal to give up on finding her father who has gone missing from the community of his mountain clan. Her kinfolk all tell her to be quiet and stop her search. She continues, nonetheless, sustaining a severe beating from the women. She wants to save her home which her father has put up for collateral for a jail bond. She also wants to raise her little brother and sister given that her father is gone and her mother is mentally ill. In the end, after her encounter with the ‘dead father’, the Big Man, who is the power behind the clan, comes to respect her. Questions of the relationship to father figures, and to the position that Ree occupies in terms of sexuation will structure the analysis of this film where, through her loyalty to the clan (“blood”) and to her father, she is portrayed as a strong female character who, Antigone-like, will not give up on her desire.